Ticks infesting humans in Central America: A review of their relevance in public health - Bermúdez C, Sergio (2022)
Ticks are blood-sucking arthropods that parasitize most groups of terrestrial or semiaquatic vertebrates. Humans are accidental hosts to the ticks; however, in humans the ticks can cause damages varying from simple irritation to severe allergies, toxicosis, paralysis, and the transmission of pathogens, some of which can be fatal. Central America represents a narrow isthmus between North and South America and is considered a biodiversity hotspot. The importance of tick-borne diseases in this region is manifested by fatal outbreaks caused by Rickettsia rickettsii, severe and mild cases of other rickettsioses, ehrlichiosis, and tick-borne relapsing fevers, in addition to cases paralysis and strong allergic reactions. Even so, this information is scarce in most countries of this region, and there are no epidemiological data. In this article we present a review of the ticks that parasitize humans in Central America, covering data from the 19th Century to the present day. Of nearly 80 tick species reported in Central America, 28 species are reported on humans. This list includes species that thrive within homes, grazing areas and, to a lesser extent, in wild environments, both in lowland and high mountain forests. The most important genus in this region is Amblyomma, followed by Rhipicephalus and Ornithodoros, and to a lesser extent Haema physalis, Ixodes and Dermacentor. These data provide information on the tick species most commonly associated with humans in Central America, and highlight the potential for tick-borne diseases in wild, rural and urban regions